The Impact of the Age of the Driver of Freight Transport on the probability of being involved in a Traffic Accident (Case Study in Krian – Taman Sidoarjo Road) - Risdianto, Dwi; Widyastuti, Hera (Fakultas Teknik Universitas Brawijaya, 2022)
Traffic accident is one of the traffic problems that caused deaths, injuries and material loses. The high number of traffic accident is an indicator of the low level of road traffic safety. Krian – Taman Sidoarjo road has become one of black site area. According to data from the Sidoarjo Resort Police, there have been 66 traffic accidents during 2015 to 2020. The majority of accidents involve freight transport compared to passenger transport. Therefore, it is necessary to conduct research to find out the factors of freight transport drivers that affect the possibility of traffic accidents in Krian – Taman Sidoarjo road. Methods of data collection using questionnaires to drivers of freight transportation. While the analystical method used is descriptive analysis and logistic regression using data from questionnaires. The result of research shows that the older the driver, the higher the probability of being involved in a traffic accident.